The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris - Shinohara, Akihiko; Kato, Yu (Zootaxa, 2017)
Based on a recently collected specimen, we describe the previously unknown female of Acantholyda flaviventris Shinohara, 1991, and give a revised key to the females of the 14 species of the genus distributed in Japan.